Involvement of the Dectin-1 Receptor upon the Effector Mechanisms of Human Phagocytic Cells against Paracoccidioides brasiliensis - Juliana Carvalho de Quaglia e Silva; Amanda Manoel Della Coletta; Taiane Priscila Gardizani; Graziela Gorete Romagnoli; Ramon Kaneno; Luciane Alarcão Dias-Melicio (Journal of Immunology Research)
Paracoccidioidomycosis (PCM), a systemic mycosis endemic in Latin America, occurs after inhalation of mycelial components of Paracoccidioides spp. When the fungus reaches the lungs and interacts with the alveolar macrophages and other cells, phagocytic cells such as neutrophils and monocytes are immediately recruited to the injured site. The interaction between surface molecules of pathogens and homologous receptors, present on the surface membrane of phagocytes, modulates the innate immune cell activation. Studies have shown the importance of fungal recognition by the Dectin-1 receptor, which can induce a series of cellular protective responses against fungi. The objective of the present study was to evaluate Dectin-1 receptor expression and the effector mechanisms of human monocytes and neutrophils activated or not with different cytokines, such as IFN-γ, TNF-α, and GM-CSF, followed by the challenge with Paracoccidioides brasiliensis (P. brasiliensis or Pb265). Therefore, analysis of Dectin-1 receptor expression was done by flow cytometry whereas the effector mechanisms were evaluated by fungal recovery by colony-forming unit (CFU) counting and hydrogen peroxide (H2O2) production. Our results showed that, after treatment with IFN-γ, TNF-α, and GM-CSF and challenge with Pb265, cells, especially monocytes, demonstrated an increase in Dectin-1 expression. Both types of cells treated with the cytokines exhibited a decreased fungal recovery and, conversely, an increased production of H2O2. However, when cultures were treated with an anti-Dectin-1 monoclonal antibody, to block the P. brasiliensis binding, a decrease in H2O2 production and an increase in fungal recovery were detected. This effect was observed in all cultures treated with the specific monoclonal antibody. These results show the involvement of the Dectin-1 receptor in fungal recognition and its consequent participation in the induction of the killing mechanisms against P. brasiliensis.